Efeito do tratamento crônico com paracetamol sobre a reatividade das vias aéreas isoladas de ratos - Ribeiro, Marco Túlio Lacerda (2018)
Background: Some studies relate the use of paracetamol with the exacerbation of asthma symptoms and other respiratory problems. Other studies are inconclusive or deny this correlation. This makes the association between paracetamol and airway hypersensitivity very controversial and still under debate. Objectives: To investigate the effect of chronic treatment with paracetamol on rats on the contraction and relaxation of isolated airways. Methods: Wistar rats were divided into 2 groups (n = 5-8). One group was treated for 2 weeks with paracetamol (400 mg / kg, v.o.) in drinking water and another control group (pure water). The animals were euthanized after two weeks, blood was collected for biochemical analyzes (ALT, AST, TBARs reaction) and tracheal rings were isolated and prepared in an organ bath to measure the isometric tension against contractile stimuli (concentration- effect for carbachol and KCl, concentration- 2+ effect curve for Ca stimulated with carbachol or KCl) and relaxants (isoprenaline, sodium nitroprusside and verapamil). Results: Liver enzymes ALT, AST and lipid peroxidation (TBARs) were significantly increased after paracetamol treatment. Acupuncture of the airway tracheal smooth muscle response does not present any alteration, either to the contractile or relaxing stimulus, for example: cholinergic agonist, membrane 2+ 2+ 2+ depolarization, Ca influx by the sarcolemma, internal release of Ca from the sarcoplasmic reticulum, Ca , β-receptor agonist or NO donor-induced relaxation. Conclusion: Chronic treatment with paracetamol does not induce hyper or hyporeativity of the airways isolated from rats.